OARSI Clinical Trials Recommendations: Design and conduct of clinical trials for hip osteoarthritis. Issue 5 (May 2015) - Lane, N.E.; Hochberg, M.C.; Nevitt, M.C.; Simon, L.S.; Nelson, A.E.; Doherty, M.; Henrotin, Y.; Flechsenhar, K.
Summary: The ability to assess the efficacy and effectiveness of an intervention for the treatment of hip osteoarthritis (OA) requires strong clinical trial methodology. This consensus paper provides recommendations based on a narrative literature review and best judgment of the members of the committee for clinical trials of hip OA. We provide recommendations on clinical trial design, outcome measures, including structural (radiography), and patient and physician global assessments, performance based measures, molecular markers and experimental endpoints including MRI imaging. This information can be utilized by sponsors of trials for new therapeutic agents for hip OA.